Social panorama of Latin America.... -2005- (UN ECLAC SantiagoCL)
Social Panorama of Latin America presents official measurements for the analysis of income poverty from the Economic Commission for Latin America and the Caribbean (ECLAC), and seeks fresh approaches to poverty and well-being, placing special emphasis on multidimensional approaches.
Documentation Centre has: 2005; 2007-'20